2004
DOI: 10.1109/tps.2004.835941
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of the Plasma Composition in the Magnetic Field Evolution in Plasma Opening Switches

Abstract: Abstract-High spatial-and temporal-resolution spectroscopic methods are employed to perform detailed studies of the interaction between the propagating magnetic field and a multi-ion-species plasma. The experiment is performed in a plasma-opening-switch configuration, in which a 150-kA current of 400 ns duration is conducted through a plasma. Recent observations demonstrated a new phenomenon of simultaneous rapid magnetic field penetration into the heavy-ion plasma and specular reflection of the light-ion plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Previous investigations of the POS operation, in which a novel method was implemented for producing plasmas of controllable purity, have been reported on. 47,48 Currently, better control of the plasma composition is pursued 49,50 in the present configuration in order to study the dependence of the phenomena observed here on this parameter. Also, improved doping capabilities should allow for further studying the mechanisms responsible for the ion velocities in the normal directions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations of the POS operation, in which a novel method was implemented for producing plasmas of controllable purity, have been reported on. 47,48 Currently, better control of the plasma composition is pursued 49,50 in the present configuration in order to study the dependence of the phenomena observed here on this parameter. Also, improved doping capabilities should allow for further studying the mechanisms responsible for the ion velocities in the normal directions.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that the proton reflection is sufficient for generating the instabilities leading to rapid field penetration raises a more general question regarding the role of the plasma composition in the plasma-magnetic field interaction. An effort to study this subject is now under way, 39 and perhaps use of controllable plasma sources ͑e.g., Ref. 45͒ can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In order to control the plasma composition, we make use of the different times of flight of ions with different charge-to-mass ratios ejected from the flashboard. In this method, 39 we mount the flashboard plasma source 4.5 cm away from the anode ͑instead of 3 cm in the previous setup͒. Due to the larger distance, the faster protons reach the A-K gap earlier than the carbon ions.…”
Section: Electron Density Distributionmentioning
confidence: 99%
“…This has the geometry more of a plasma opening switch, and cases could be found where the ions acquired a velocity component perpendicular to the J × B force. In a plasma opening switch geometry Osin et al [676] with 150 kA of 400 ns duration showed a marked difference of behaviour of the two ion species; rapid magnetic field penetration into the heavy-ion plasma and specular reflection of the light-ion plasma, leading to ion-species separation.…”
Section: Multi-species Ion Separationmentioning
confidence: 99%